Factors Influencing Students’ Willingness to Choose Blended Learning in Higher Education - Zhang, Youliang (Blended Learning. Education in a Smart Learning Environment, 2020)
Students’ willingness to participate blended leaning has been an interesting topic in the higher education context. This paper aims to examine students’ willingness to choose blended learning and identify the influencing factors related to their willingness. A large-scale questionnaire survey was conducted with a collection of 1903 valid responses. Meanwhile, nine students were interviewed. The findings indicated that blended learning have not been widely offered in Chinese universities. Students’ participation and understanding of blended learning are relatively limited, but most students have a positive attitude to blended learning and are willing to choose it in the future. Such factors as students’ demographic features, curriculum cognition, curriculum design, learning demands will affect their willingness to choose blended learning.